APLIKASI ALGORITMA FLOYD-WARSHALL DENGAN PENDEKATAN MADM DALAM MENENTUKAN RUTE TERPENDEK PENGANGKUTAN SAMPAH - Zulmagfir Buako; Lailany Yahya; Novianita Achmad (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2021)
Currently, the problem of environmental hygiene caused by the accumulation of garbage becomes a serious problem for every community. In addressing this problem, an efficient waste transport process is required. This study aims to find the shortest route of garbage transportation in Gorontalo city by using Floyd Warshall Algorithm by finding the smallest weight between each point (Vertex). In this study, the weights used in the Floyd Warshall Iteration Algorithm were Alternative weights obtained by the Multi-Attribute Decision-Making approach (MADM). The criteria for determining weights in MADM use three indicators that affect the efficiency of garbage transportation, namely Distance, time, and congestion. The route used in this study is the dump truck route with 17 garbage transportation points. After obtaining the Alternate weight and iteration using Floyd Warshall algorithm obtained the shortest route with the smallest trajectory weight of 110.845.